Expatriating the universal: a decolonial imagination beyond authentic “Asia” - Hino, Aya (International quarterly for Asian studies, 2019)
In the field of urban studies, there has been a call to develop “new geographies of theory” to accommodate “Asian” experiences of urbanisation in theory-building practices, which are said to have been based largely on “Western” experiences of urban space. In thinking about possibilities of a theory from “Asia”, this article, instead of arguing from within the field of urban studies per se, problematises the conventions of knowledge production today, including the division between the disciplines and area-centric research in the institutional formation of knowledge production, the separation of universal from particular forms of knowledge, and the isomorphism of “the West” with the universal and of “Asia” with the particular. In doing so, the author argues for the need to move beyond the notion of authentic “Asia” as an alternativelocus of enunciation vis-à-vis “the West” and to expatriate the universal from the territorially bounded place. A theory from “Asia” should embody the liminality of “Asia” and “the West” and express the universal not as the transcendence of the particular, but as the manifestation of the multitude of alterity.